Traditional Malaria Eye Drops Treatment Measures Based on Local Knowledge (Study in Manusa Village, Inamosol District) - Joma Chyntia Lattu; Mateus Sakundarno Adi; Dwi Sutiningsih (Jurnal Penelitian Pendidikan IPA, 2025)
This study analyzed traditional eye drop treatment based on local knowledge in Manusa Village, West Seram Regency, which is known as a malaria endemic area. The research method used a descriptive design with a cross-sectional approach, the validity of the instrument showed a calculated r value > r table, and reliability showed a Cronbach's Alpha value = 0.754. The results of the study revealed that 81.4% of the community believed this treatment was safe and passed down from generation to generation, 95.1% did not report any dangerous reactions, and 100% believed Kenar leaves could cure malaria. As many as 48% of the community reported no longer being positive for malaria after using this method. This traditional treatment is considered effective, safe, and based on local resources.